German and Asian Perspectives on Company Law Law and Policy Perspectives - Fleischer, Holger; Kono, Toshiyuki (Mohr Siebeck, 2023)
This volume is based on presentations delivered at a symposium held in May 2015 at the Max Planck Institute for Comparative and International Private Law in Hamburg. It seeks to reinvigorate the scholarly exchange which can be traced back to the late 19th century between company law academics in Germany, China, Japan and South Korea. Contributions from all four jurisdictions include papers on directors' liability and capital maintenance as well as studies of the role of shareholders in public companies and the regulation of groups of companies.